2018
DOI: 10.3390/cells7120257
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of EGFR Endocytosis by CBL During Mitosis

Abstract: The overactivation of epidermal growth factor (EGF) receptor (EGFR) is implicated in various cancers. Endocytosis plays an important role in EGFR-mediated cell signaling. We previously found that EGFR endocytosis during mitosis is mediated differently from interphase. While the regulation of EGFR endocytosis in interphase is well understood, little is known regarding the regulation of EGFR endocytosis during mitosis. Here, we found that contrary to interphase cells, mitotic EGFR endocytosis is more reliant on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 102 publications
(178 reference statements)
0
13
0
Order By: Relevance
“…Redundancy of endocytic pathways is not a new idea and work in this area has been pioneered with EGFR (Sigismund et al, 2005). Interestingly, we found that while clathrin knockdown increased CXCR4 PTM, this was not the case for EGFR as the antibody used to measure total EGFR has been previously shown to not be sensitive to EGFR PTMs (Wee and Wang, 2018) and previous research suggests that EGFR PTMs are unaffected by clathrin inhibition (Garay et al, 2015). Additionally, while EGFR is preferentially internalized by CME at increasing high ligand levels, at times it is also internalized by clathrin-independent mechanisms (Sigismund et al, 2005).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Redundancy of endocytic pathways is not a new idea and work in this area has been pioneered with EGFR (Sigismund et al, 2005). Interestingly, we found that while clathrin knockdown increased CXCR4 PTM, this was not the case for EGFR as the antibody used to measure total EGFR has been previously shown to not be sensitive to EGFR PTMs (Wee and Wang, 2018) and previous research suggests that EGFR PTMs are unaffected by clathrin inhibition (Garay et al, 2015). Additionally, while EGFR is preferentially internalized by CME at increasing high ligand levels, at times it is also internalized by clathrin-independent mechanisms (Sigismund et al, 2005).…”
Section: Discussionmentioning
confidence: 70%
“…Cycloheximide chase experiments in RPE cells overexpressing c-terminal myc tagged CXCR4 further confirmed that clathrin knockdown did not lead to a change in CXCR4 degradation kinetics (Supplementary Figures 3C,D) and additionally total CXCR4 labeling using the myc antibody confirmed that CXCR4 total protein levels were unchanged in the overexpression CXCR4 model as well (Supplementary Figure 3E). To test whether this phenomenon was specific to CXCR4 or more broadly applicable to other receptors, we measured EGFR protein levels using an antibody (A-10 clone) not expected to be sensitive to receptor PTM (Wee and Wang, 2018). Interestingly, clathrin knockdown significantly reduced EGFR detection in both HeLa and RPE cells as well.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, other NCE pathways remain active during mitosis, such as the one responsible for the uptake of the EGFR [130,131], as well as some macropinocytic events [132].…”
Section: Role Of Endocytosis and Trafficking In The Regulation Of Pm mentioning
confidence: 99%
“…Non-clathrin-mediated endocytosis plays a major role in the regulation of EGFR fate by targeting it to lysosomes for degradation. 9 Wang et al also reported that EGFR is degraded through the proteasome pathway. 40 We used As mentioned above, the ubiquitination regulation of EGFR by Cbl is either directly, through binding to its pY1045 site, or indirectly, through Grb2 binding to the pY1068 or pY1086 site.…”
Section: G Protein Pathway Suppressor 2 Suppresses the Growth Xenograft Gc Tumors In Vivomentioning
confidence: 98%
“…EGFR‐mediated cell signaling and its endocytosis are strictly regulated. 9 The endocytosis of EGFR can lead to two different fates of this receptor: circulation back to the plasma membrane or degradation in lysosomes. 10 Promoting EGFR degradation could be a potential strategy for tumor treatment.…”
Section: Introductionmentioning
confidence: 99%